2012
DOI: 10.3109/07420528.2012.719961
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Blood Pressure Variations Are Associated with Changes in Distal–Proximal Skin Temperature Gradient

Abstract: It is generally assumed that skin vascular resistance contributes only to a small extent to total peripheral resistance and hence to blood pressure (BP). However, little is known about the impact of skin blood flow (SBF) changes on the diurnal variations of BP under ambulatory conditions. The main aim of the study was to determine whether diurnal patterns of distal SBF are related to mean arterial BP (MAP). Twenty-four-hour ambulatory measurements of BP, heart rate (HR) and distal (mean of hands and feet) as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 63 publications
4
26
1
Order By: Relevance
“…Based on previous findings [19] we applied a multilevel structural equation model to explain changes in MAP by changes in PET and ST. Path-analysis was performed by a two-level model with measurements nested within participants [26]. In this model person mean centering is used by default, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous findings [19] we applied a multilevel structural equation model to explain changes in MAP by changes in PET and ST. Path-analysis was performed by a two-level model with measurements nested within participants [26]. In this model person mean centering is used by default, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study under structured ambulatory conditions it could be shown that mean arterial BP exhibits an inverse 24 h pattern to STs most pronounced in distal skin regions in relation to proximal skin regions [19,20]. Unfortunately, no direct measurements of PET were recorded preventing detailed analyses and interpretation with respect to temporal changes in PET and its association with STs and BP.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…56 A study on human subjects claimed that the more negative are the values of DPG during daytime activities, the greater is the nocturnal ABP dipping. 55 This suggests that changes in skin SNA may play a key causal role in driving the changes in ABP during NREM sleep. However, evidence on experimental models does not appear consistent with this suggestion.…”
Section: Changes In Skin Temperature Upon Awakening From Nrem Sleepmentioning
confidence: 99%
“…Accordingly, human subjects reportedly show a relative vasodilation of distal (wrist and ankles) skin compared with proximal (infraclavicular and sternal) skin during sleep, so that the temperature difference between distal and proximal skin sites, termed the distal-proximal skin temperature gradient (DPG), becomes less negative and tends to 0 during sleep. 55 Upon awakening from sleep, conversely, the DPG rapidly becomes negative again, mainly because of a decrease in distal skin temperature. 56 A study on human subjects claimed that the more negative are the values of DPG during daytime activities, the greater is the nocturnal ABP dipping.…”
Section: Changes In Skin Temperature Upon Awakening From Nrem Sleepmentioning
confidence: 99%